'Is the current foreign exchange regime in Jamaica optimal?' - Ghartey, Edward E. ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Examines the extenal imbalance of Jamaica by estimating exchange market pressure, and measuring the degree to which the Bank of Jamaica in the cureent global environment can pursue independent monetary policies with the tools of both open market operation and discounting policies.